Body size and season influence elemental composition of tissues in ocean sunfish Mola mola juveniles. (May 2019) - Baptista, Miguel; Azevedo, Olga; Figueiredo, Cátia; Paula, José Ricardo; Santos, Marta Tiago; Queiroz, Nuno; Rosa, Rui; Raimundo, Joana
Abstract: The effects of body size and season on the elemental composition of ocean sunfish Mola mola were assessed for the first time. A total of 57 by-caught juvenile specimens measuring between 31.8 and 120.3 cm were sampled in spring and autumn. Concentrations of trace elements (three essential - Co, Cu, Zn, and three non-essential - As, Cd, Pb) were determined in five body tissues [gills, gelatin (subcutaneous white gelatinous layer), liver, white muscle and red muscle]. Elemental composition of M. mola tissues was found to vary with both body size and season. When an effect of size was verified, the most common trend was a decrease in elemental levels with increasing fish size, most likely deriving from the fast growth rate of this fish (i.e. dilution effect) and the occurrence of an ontogenetic shift in dietary preferences. Differently, Zn levels increased with fish size in both gills and red muscle, potentially deriving from a greater physiological need in those tissues as fish grow. Seasonal differences in trace element levels were observed for approximately half of the studied cases (tissue/trace element) with greater elemental concentrations being mostly found in autumn. Such pattern was most obvious in liver tissue, presumably resulting from a greater dietary elemental uptake in the end of summer/autumn. A general absence of seasonal differences was observed in the gills, white muscle and red muscle. Interestingly, a trend of enhanced concentrations in spring was observed for gelatin, potentially deriving from past long-term differences in exposure to trace elements. Highlights: Elemental composition of Mola mola tissues was found to vary with both body size and season. Most common size effect was trace element concentration decreasing with fish growth. Zn levels increased with fish size in both gills and red muscle. Greater elemental concentrations were mostly found in Autumn, especially in the liver. A general absence of seasonal differences was observed in the gills, white muscle and red muscle.